Otherness in el arco y la lira by octavio paz [La otredad en el arco y la lira de octavio paz] (2019)
The aim of this article is to carry out a study on the theory of otherness in three essays from the book El arco y la lira by Octavio Paz: “La otra orilla”, “La inspiración” and “Los signos en rotación”. Given that the otherness is a philosophical problem that dates back to ancient times, a theoretical frame was included in order to expose a background, adopt a methodology and formulate a hypothesis regarding the characteristics of Paz’ theory. The hypothesis suggests that a certain affinity can be found with Hegel’s dialectics in that for Paz the search for otherness is a dialectical process between being and non-being, between the self and the non-self (the other), and later on this supposition was confirmed in the analysis. Furthermore, three different and complementary visions on otherness were found in the three essays: In “La otra orilla”, Paz argues that the poetic revelation is similar to the religious one insofar as it entails an act of “plunging into the other”; in “La inspiración”, he adopts a surrealist perspective, according to which the poetic experience implies a “fusion with the other”; and, finally, in “Los signos de rotación”, most similarities with Hegel were disclosed, especially when Paz suggests that the other should be associated with “being as change”, rejecting the traditional idea of “death”. © 2019, Universidad Complutense de Madrid. All rights reserved.